2019
DOI: 10.1111/opo.12659
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime driving: visual, lighting and visibility challenges

Abstract: Purpose Nighttime driving is dangerous and is one of the most challenging driving situations for most drivers. Fatality rates are higher at night than in the day when adjusted for distances travelled, particularly for crashes involving pedestrians and cyclists. Although there are multiple contributory factors, the low light levels at night are believed to be the major cause of collisions with pedestrians and cyclists at night, most likely due to their reduced visibility. Understanding the visibility problems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 144 publications
(397 reference statements)
1
41
0
Order By: Relevance
“…Despite these apparent benefits, the survey also found a residual demand for further street lighting to be provided. This would support the suggestion that drivers rely most heavily on their photopic visual acuity, and that situations in which mesopic vision is important such as night driving are more problematic, particularly for elderly users [56,57]. Establishment of a fully lit road network would be impractical both in cost and environmental terms and in this regard compromises are inevitable.…”
Section: Discussionmentioning
confidence: 64%
“…Despite these apparent benefits, the survey also found a residual demand for further street lighting to be provided. This would support the suggestion that drivers rely most heavily on their photopic visual acuity, and that situations in which mesopic vision is important such as night driving are more problematic, particularly for elderly users [56,57]. Establishment of a fully lit road network would be impractical both in cost and environmental terms and in this regard compromises are inevitable.…”
Section: Discussionmentioning
confidence: 64%
“…Based on research on autonomous or non-autonomous cars, on different communication technologies, on decentralized and centralized connectivity [45,46], we have concluded that there is a rich cluster of information and interaction produced between vehicles and other road entities. In the Solution section, we are going to explore a dynamic visualization [47] of road information in terms of predictive weather conditions [48], visibility [49,50] and outdoor illumination [51,52] and potential sun glares [53,54] at the future moment of passing through that area, with markings on possible hazards [55,56], for a better trip planning. We chose this kind of information compared to the better-known real-time crowd sourced [57] traffic data, as an example of a novel cluster of visualized road information.…”
Section: Connected Cars and Smart Transport Infrastructurementioning
confidence: 99%
“…Driving performance can be severely impaired at night due to low (mesopic) illumination. 9,10 Visual challenges associated with nighttime driving is further worsened by the headlights of on-coming vehicles. [11][12][13][14] Straylight from headlights can reduce retinal image contrast which manifests as either dazzling glare or scotomatic glare.…”
Section: Introductionmentioning
confidence: 99%